"Fortunate are those who take the first steps"? The psychosocial impact of novel drug development. (August 2019) - Dobra, Rebecca; Madge, Susan; Martin, Isaac; Weldon, Paul; Simmonds, Nicholas; Davies, Jane C.
Abstract: Novel drug development offers people with cystic fibrosis exciting opportunities but is not without challenges. Currently, there is an understandable emphasis on protecting patients' physical health when developing treatments. However, there appears to be little consideration of how novel drug development impacts on psychosocial wellbeing, or the downstream consequences of this. Using an illustrative case and reviewing the literature we explore themes regarding the psychosocial impact of trial participation and novel drug development and identify areas requiring further research. Through this, we hope to prepare healthcare professionals to better understand the needs of their patients in this rapidly evolving landscape.